Higher levels of Pseudomonas aeruginosa LasB elastase expression are associated with early-stage infection in cystic fibrosis patients - Agustina Llanos; Pauline Achard; Justine Bousquet; Clarisse Lozano; Magdalena Zalacain; Carole Sable; Hélène Revillet; Marlène Murris; Marie Mittaine; Marc Lemonnier; Martin Everett (Scientific Reports, 2023)
Abstract Pseudomonas aeruginosa is a common pathogen in cystic fibrosis (CF) patients and a major contributor to progressive lung damage. P. aeruginosa elastase (LasB), a key virulence factor, has been identified as a potential target for anti-virulence therapy. Here, we sought to differentiate the P. aeruginosa isolates from early versus established stages of infection in CF patients and to determine if LasB was associated with either stage. The lasB gene was amplified from 255 P. aeruginosa clinical isolates from 70 CF patients from the Toulouse region (France). Nine LasB variants were identified and 69% of the isolates produced detectable levels of LasB activity. Hierarchical clustering using experimental and clinical data distinguished two classes of isolates, designated as ‘Early’ and ‘Established’ infection. Multivariate analysis revealed that the isolates from the Early infection class show higher LasB activity, fast growth, tobramycin susceptibility, non-mucoid, pigmented colonies and wild-type lasR genotype. These traits were associated with younger patients with polymicrobial infections and high pFEV1. Our findings show a correlation between elevated LasB activity in P. aeruginosa isolates and early-stage infection in CF patients. Hence, it is this patient group, prior to the onset of chronic disease, that may benefit most from novel therapies targeting LasB.